Not another hillshade: alternatives which improve visualizations of bathymetric data - Novak, Ana; Poglajen, Sašo; Vrabec, Marko (Frontiers in Marine Science, 2023)
Increasing awareness of the importance of effective communication of scientific results and concepts, and the need for more accurate mapping and increased feature visibility led to the development of novel approaches to visualization of high-resolution elevation data. While new approaches have routinely been adopted for land elevation data, this does not seem to be the case for the offshore and submerged terrestrial realms. We test the suitability of algorithms provided by the freely-available and user-friendly Relief Visualization Toolbox (RVT) software package for visualizing bathymetric data. We examine the algorithms optimal for visualizing the general bathymetry of a study area, as well as for highlighting specific morphological shapes that are common on the sea-, lake- and riverbed. We show that these algorithms surpass the more conventional analytical hillshading in providing visualizations of bathymetric data richer in details, and foremost, providing a better overview of the morphological features of the studied areas. We demonstrate that the algorithms are efficient regardless of the source data type, depth range, resolution, geographic, and geological setting. The summary of our results and observations can serve as a reference for future users of RVT for displaying bathymetric data.